2021
DOI: 10.3389/fcimb.2020.611801
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Roles of the Inner Membrane Complex in the Multiple Stages of the Malaria Parasite

Abstract: Apicomplexan parasites, such as human malaria parasites, have complex lifecycles encompassing multiple and diverse environmental niches. Invading, replicating, and escaping from different cell types, along with exploiting each intracellular niche, necessitate large and dynamic changes in parasite morphology and cellular architecture. The inner membrane complex (IMC) is a unique structural element that is intricately involved with these distinct morphological changes. The IMC is a double membrane organelle that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 145 publications
(192 reference statements)
0
53
0
Order By: Relevance
“…This is reflected in the architecture and proteome of the IMC. For apicomplexans, the IMC has three main functions: (a) it plays a major role in motility and invasion, (b) it confers stability and shape to the cell and (c) it provides a scaffolding framework during cytokinesis (Ferreira et al, 2021; Harding & Frischknecht, 2020). While the IMC of the motile stages serves as the anchor for proteins involved in gliding motility and host cell invasion (Baum, Gilberger, Frischknecht, & Meissner, 2008; Perrin et al, 2018; Soldati, Foth, & Cowman, 2004), the gametocyte IMC appears to serve a structural role (Dearnley et al, 2012; Parkyn Schneider et al, 2017; Sinden, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reflected in the architecture and proteome of the IMC. For apicomplexans, the IMC has three main functions: (a) it plays a major role in motility and invasion, (b) it confers stability and shape to the cell and (c) it provides a scaffolding framework during cytokinesis (Ferreira et al, 2021; Harding & Frischknecht, 2020). While the IMC of the motile stages serves as the anchor for proteins involved in gliding motility and host cell invasion (Baum, Gilberger, Frischknecht, & Meissner, 2008; Perrin et al, 2018; Soldati, Foth, & Cowman, 2004), the gametocyte IMC appears to serve a structural role (Dearnley et al, 2012; Parkyn Schneider et al, 2017; Sinden, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…To date about 45 IMC proteins have been identified in Plasmodium (Ferreira et al, 2021), however, there is no comprehensive proteomic analysis of this structure available. From the confirmed IMC proteins it is evident that in addition to a common core set of conserved proteins found in all Alveolata, such as the Alveolins (Gould et al, 2011; Gould, Tham, Cowman, McFadden, & Waller, 2008), the IMC includes many lineage‐specific proteins, reflecting additional specialized roles (Kono et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…an anchor for the motor complex, playing a significant role in gliding and thus invasion [5,15]. A number of studies have identified several proteins associated with the IMC and have provided insights into the organization and roles of the glideosome complex [5][6][7][16][17][18]. The basic motor complex in apicomplexan parasites that drives gliding motility and invasion is comprised of conserved components such as actin-MyoA-MTIP-GAP45-GAP40-GAP50--GAPMs-adhesin protein.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The IMC of an Apicomplexan parasite plays diverse roles in maintaining the structural stability of the zoite forms. It also acts as a scaffold for daughter cell development and plays a key role in motility and host-cell invasion [6,7]. Proteins involved in the organization of pellicle/IMC/glideosome include structural proteins such as alveolins (IMC1a-h), glideosome associated protein-40, -45, and -50 and glideosome associated proteins with multiple membrane spans (GAPMs), ISPs and these proteins together with MTIP (Myosin A tail domain interacting protein) anchor the actomyosin motor complex to the IMC [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation